2016
DOI: 10.1016/j.foodchem.2015.07.151
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the recovery of tiger nut (Cyperus esculentus) oil by mechanical pressing: Moisture content, particle size, high pressure and enzymatic pre-treatment effects

Abstract: Tiger nut (Cyperus esculentus) tuber contains oil that is high in monounsaturated fatty acids, and this oil makes up about 23% of the tuber. The study aimed at evaluating the impact of several factors and enzymatic pre-treatment on the recovery of pressed tiger nut oil. Smaller particles were more favourable for pressing. High pressure pre-treatment did not increase oil recovery but enzymatic treatment did. The highest yield obtained by enzymatic treatment prior to mechanical extraction was 33% on a dry defatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 33 publications
0
44
0
Order By: Relevance
“…The total tocopherols of the oil samples in this study were determined using an high‐performance liquid chromatography‐ultraviolet (HPLC‐UV) system (Agilent 1200, Manchester, UK) following the method used by Ezeh et al . (2016) and Costa et al . (2010) with slight modifications.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The total tocopherols of the oil samples in this study were determined using an high‐performance liquid chromatography‐ultraviolet (HPLC‐UV) system (Agilent 1200, Manchester, UK) following the method used by Ezeh et al . (2016) and Costa et al . (2010) with slight modifications.…”
Section: Methodsmentioning
confidence: 96%
“…The fatty acid composition (FAC) of MO oil was determined using the method described by Ezeh et al . (2016), with slight modifications. Gas chromatography (GC, Agilent HP 6890) fitted with flame ionization detector (FID) was used for the analysis, with a Varian CP‐Sil 88 fused silica capillary column (60 m × 0.25 mm × 0.20 μm) and helium as a carrier gas (flowrate 1.0 mL min −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Jung & Mahfuz (2009) stated that the use of HPP at 200 MPa and 500 MPa, followed by AEE (protease enzyme), resulted in 3.20% and 1.30% (w/w) higher soybean oil yield, respectively, under otherwise identical conditions. In the case of tiger nuts on the other hand, Ezeh et al (2016) reported no significant difference in the oil yield from an AEE alone and from AEE with HPP pre-treatment at 50-700 MPa. It was reported that the parenchyma cells of the tubers exhibit cross linking of diferulic acid with arabinoxylans which contribute to its tough texture, even tougher than potatoes (Parker et al, 2000), thus the tuber's cells were not affected by the HPP pre-treatment.…”
Section: Introductionmentioning
confidence: 91%
“…The chemical and physical composition, characteristics and physiochemical properties of Cyperus esculentus have been shown in the various literature (Ezeh et al 2016;Li et al 2017;Chinma et al 2009;Codina-Torrella et al 2015;Ocloo et al 2014). Lopéz-Cortés et al (2013) and Ezeh et al (2016) in their studies identified that Tiger nut has the capacity to provide good amounts of fatty acids. This property makes it a good lubricant additive in drilling fluids which helps to reduce friction generated during the drilling operations.…”
Section: Introductionmentioning
confidence: 99%